The Merelani Graphite-Tanzanite Deposit, Tanzania: An Exploration Case History (f453b99b-0704-440a-8188-3812d53498c1) - C. Davies; R. J. Chase (Canadian Institute of Mining, Metallurgy and Petroleum, 1994)
"The Merelani graphite-tanzanite deposit is located in northeast Tanzania, 14 kilometers south of Kilimajaro International Airport and in close proximity to the towns of Moshi and Arusha. The graphite mineralization is hosted by relatively undeformed linear Proterozoic metasedimentary gneisses, several of which have been subjected to hydrothermal alteration resulting in tanzanite mineralization. Exploration work comprised detailed geological mapping coupled with pit and trench channel sampling and a subsequent 1500 meters of diamond drilling. In addition, metallurgical tests have shown the graphite to be of unusually coarse flake size, crystallinity and high purity.Feasability studies have shown the economic viability of a major coarse flake graphite deposit with the measured resource to 50 meters in excess of 9 million tonnes assaying over 85 graphitic carbon. Production is due to start by the end of the first quarter of 1994 with the processing plant design capacity initially set at 15 000 tonnes per annum.In addition to graphite production, tanzanite will be produced through selective mining within the graphite open pit in the upper horizon and from underground workings within the lower horizon.The Merelani graphite-tanzanite deposit will be the first major orebody to be exploited through means of private funding since Tanzania gained independence"